THE IMPACT OF ISLAMIC MICROFINANCE UPON POVERTY ALLEVIATION BY THE DEVELOPMENT OF MICROENTERPRISES IN MAURITANIA - Mokhtar Maouloud , Vatimetou (Online Journal of Islamic Management and Finance (OJIMF), 2023)
Even though Islamic microfinance has proved to have a positive impact o poverty and microenterprises, there is a lack of studies on this topic in the case of Mauritania. This research attempts to study the role of Islamic microfinance (IsMF) products’ usage on poverty alleviation through the mediation effect of microenterprises development (MEs) in Nouakchott-Mauritania. This quantitative study uses primary data collected from 381 beneficiaries of the IsMF institution PROCAPEC in Nouakchott through a cross-sectional time horizon design survey. Structural equation modelling (SEM) is used to test the hypothesis through the AMOS 23 software. Findings reveal that the usage of IsMF products has a positive impact on MEs. Also, it has been found that MEs have a positive impact on poverty alleviation by reducing its five dimensions (income, education, health, expenditure, and assets ownership). The results show that the MEs has a full mediation effect on the relationship between the IsMF products’ usage and income, education, health, and expenditure; however, it has a partial mediation effect on the relationship of usage and assets. This study is among the pioneer to discuss this topic in the geographical context of Mauritania, where a scarcity of studies exists. It is recommended that policymakers adopt strategies enhancing the usage of Islamic microfinance products. The Mauritanian government is encouraged to develop the microenterprises sector to alleviate poverty in the country.